2003
DOI: 10.1002/bem.10103
|View full text |Cite
|
Sign up to set email alerts
|

Radio frequency electromagnetic field exposure in humans: Estimation of SAR distribution in the brain, effects on sleep and heart rate

Abstract: In two previous studies we demonstrated that radiofrequency electromagnetic fields (RF EMF) similar to those emitted by digital radiotelephone handsets affect brain physiology of healthy young subjects exposed to RF EMF (900 MHz; spatial peak specific absorption rate [SAR] 1 W/kg) either during sleep or during the waking period preceding sleep. In the first experiment, subjects were exposed intermittently during an 8 h nighttime sleep episode and in the second experiment, unilaterally for 30 min prior to a 3 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
111
3
7

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(132 citation statements)
references
References 54 publications
11
111
3
7
Order By: Relevance
“…The model is based on a data set of the head of a healthy female subject (aged 40 years), consisting of 121 magnetic resonance images (MRI), with a slice separation of 1 mm in the ear region and 3 mm for the rest of the head [Burkhardt and Kuster, 2000]. During the MRI scans, the pinna of the ear was [Haarala et al, 2003[Haarala et al, , 2004[Haarala et al, , 2005[Haarala et al, , 2006 Swinburne Setup [Loughran et al, 2005] Zurich Setup [Huber et al, 2000[Huber et al, , 2002[Huber et al, , 2003[Huber et al, , 2005Regel et al, 2006Regel et al, , 2007 Huber et al [2000Huber et al [ , 2002Huber et al [ , 2003Huber et al [ , 2005; Regel et al [2007] Set for psSAR10g b ¼ 0.2 and 5 W/kg in Regel et al [2006] a Power control level (PCL), corresponding to a nominal output power of 33dBm AE4 dB [ETSI-3GPP, 2005]. Note that for most phones the actual input power is towards the lower end of the accepted range.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The model is based on a data set of the head of a healthy female subject (aged 40 years), consisting of 121 magnetic resonance images (MRI), with a slice separation of 1 mm in the ear region and 3 mm for the rest of the head [Burkhardt and Kuster, 2000]. During the MRI scans, the pinna of the ear was [Haarala et al, 2003[Haarala et al, , 2004[Haarala et al, , 2005[Haarala et al, , 2006 Swinburne Setup [Loughran et al, 2005] Zurich Setup [Huber et al, 2000[Huber et al, , 2002[Huber et al, , 2003[Huber et al, , 2005Regel et al, 2006Regel et al, , 2007 Huber et al [2000Huber et al [ , 2002Huber et al [ , 2003Huber et al [ , 2005; Regel et al [2007] Set for psSAR10g b ¼ 0.2 and 5 W/kg in Regel et al [2006] a Power control level (PCL), corresponding to a nominal output power of 33dBm AE4 dB [ETSI-3GPP, 2005]. Note that for most phones the actual input power is towards the lower end of the accepted range.…”
Section: Methodsmentioning
confidence: 99%
“…The latter was motivated by the hypothesis that sub-cortical regions (including the thalamus) may contain the structures most sensitive to RF EMF. Because the EEG effect did not depend on the side of exposure [Huber et al, 2000[Huber et al, , 2003 it was hypothesized that bilateral cortical projections from sub-cortical structures may explain the absence of a hemispheric asymmetry. For validation, the same phantoms as defined for compliance testing [IEC, 2007] were used, that is, a flat phantom, and the specific anthropomorphic mannequin (SAM).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Huber et al [8] reported an extended analysis of the two studies as well as the detailed dosimetry of the brain areas, including the assessment of the exposure variability and uncertainties. The latter enabled a more in depth analysis and discussion of the findings.…”
Section: Human Studiesmentioning
confidence: 99%